Characterization of FosA13, a novel fosfomycin glutathione transferase identified in a Morganella morganii isolate from poultry - Zhang, Runzhi; Yu, Yan; Huang, Lulu; Chen, Susu; Hu, Ruxi; Wang, Xiuxiu; Huang, Dawei; Song, Chunhan; Lu, Junwan; Bao, Qiyu; Hu, Yunliang; Jiang, Pengfei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundM. morganii is a species of the genus Morganella in the family Enterobacteriaceae. This species primarily causes infections of postoperative wounds and the urinary tract. Some isolates of M. morganii exhibit resistance to multiple antibiotics due to multidrug resistance traits, complicating clinical treatment; thus, there is a growing need to elucidate the resistance mechanisms of this pathogen.MethodsA total of 658 bacterial strains were isolated from anal fecal swabs from poultry and livestock and from the surrounding environment in Wenzhou, China, via plate streaking. The full genome sequences of the bacteria were obtained via next-generation sequencing platforms. The standard agar dilution method was employed to determine the minimum inhibitory concentrations (MICs) of various antimicrobial agents. The resistance gene (fosA13) of the isolate was identified using the Comprehensive Antibiotic Resistance Database (CARD) and confirmed via molecular cloning. The FosA13 protein encoded by the novel resistance gene fosA13 was expressed with the vector pCold I, and its enzyme kinetics parameters were characterized. The genetic background and evolutionary process of the sequence of this novel resistance gene were analyzed by means of bioinformatics methods.ResultsIn this study, we identified a new chromosomally encoded fosfomycin resistance gene, designated fosA13, from the M. morganii isolate DW0548, which was isolated from poultry on a farm in Wenzhou, China. Compared with the control strain (pUCP19/DH5α), the recombinant strain carrying fosA13 (pUCP19-fosA13/DH5α) presented a fourfold increase in the MIC value for fosfomycin. The enzyme kinetics data of FosA13 revealed effective inactivation of fosfomycin, with a kcat/Km of (1.50 ± 0.02)×104 M-1·s-1. Among functionally characterized resistance proteins, FosA13 presented the highest amino acid (aa) homology (55.6%) with FosA. FosA13 also contained essential functional residues of FosA proteins. The isolate M. morganii DW0548 presented high MIC values (≥ 8 μg/mL) for 5 classes of antimicrobials, namely, aminoglycosides, β-lactams, quinolones, tetracycline, and chloramphenicol, but only two functionally characteristic antimicrobial resistance genes (ARGs) have been identified in the complete genome: a β-lactam resistance gene (blaDHA-16) and a phenol resistance gene (catII). These findings indicate that in addition to the novel resistance gene identified in this work, other uncharacterized resistance mechanisms might exist in M. morganii DW0548.ConclusionA novel chromosomal fosfomycin resistance gene, fosA13, was identified in an animal M. morganii isolate, and its enzymatic parameters were characterized. This protein shares the highest aa identity of 55.6% with the functionally characterized protein FosA and has all the essential functional residues of FosA proteins. Exploring more antimicrobial resistance mechanisms of this pathogen would help clinicians choose effective drugs to treat infectious diseases in animal husbandry and clinical practice and facilitate the development of methods to prevent the spread of resistance between bacteria of different species.